Renovación y revitalización urbana del sector noroccidental del municipio de Pitalito, Huila (2020)
The purpose of this research is to make citizen participation important for the comprehensive improvement of the urban structure, where a renewal and revitalization treatment is generated in this important sector of the municipality of Pitalito. The research is carried out through urban studies, which allow interpreting the problems related to the urban context that currently lacks sports, health, commerce and public space facilities. In response to the above, an urban proposal is generated with the implementation of multifamily housing of social interest and the comprehensive improvement of existing facilities such as the Olympic village, the market square and the municipal slaughterhouse and the revitalization of areas that lack space public, which will be consolidated with the proposed and existing housing, where the design of this urban proposal is based on the development treatments indicated by the regulations, in order to mitigate the problems encountered and through these solutions, meet the needs of the inhabitants of the northwestern sector and the municipality of Pitalito Huila.